Search for supersymmetry in the multijet and missing transverse momentum final state in pp collisions at 13 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Ivanov, Andrew; et al. (My University, 2016)
A search for new physics is performed based on all-hadronic events with large missing transverse momentum produced in proton-proton collisions at s=13 TeV. The data sample, corresponding to an integrated luminosity of 2.3 fb-1, was collected with the CMS detector at the CERN LHC in 2015. The data are examined in search regions of jet multiplicity, tagged bottom quark jet multiplicity, missing transverse momentum, and the scalar sum of jet transverse momenta. The observed numbers of events in all search regions are found to be consistent with the expectations from standard model processes. Exclusion limits are presented for simplified supersymmetric models of gluino pair production. Depending on the assumed gluino decay mechanism, and for a massless, weakly interacting, lightest neutralino, lower limits on the gluino mass from 1440 to 1600 GeV are obtained, significantly extending previous limits. © 2016 The Author.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Woods, N. (2016). Search for supersymmetry in the multijet and missing transverse momentum final state in pp collisions at 13 TeV. Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 758, 152-180. doi:10.1016/j.physletb.2016.05.002
Additional Authors: Friedl, M.;Fruehwirth, R.;Ghete, V. M.;Hartl, C.;Hörmann, N.;Hrubec, J.;Jeitler, M.;König, A.;Krätschmer, I.;Liko, D.;Matsushita, T.;Mikulec, I.;Rabady, D.;Rad, N.;Rahbaran, B.;Rohringer, H.;Schieck, J.;Strauss, J.;Treberer-Treberspurg, W.;Waltenberger, W.;Wulz, C. E.;Mossolov, V.;Shumeiko, N.;Suarez Gonzalez, J.;Alderweireldt, S.;Cornelis, T.;De Wolf, E. A.;Janssen, X.;Knutsson, A.;Lauwers, J.;Luyckx, S.;Van De Klundert, M.;Van Haevermaet, H.;Van Mechelen, P.;Van Remortel, N.;Van Spilbeeck, A.;Abu Zeid, S.;Blekman, F.;D'Hondt, J.;Daci, N.;De Bruyn, I.;Deroover, K.;Heracleous, N.;Lowette, S.;Moortgat, S.;Moreels, L.;Olbrechts, A.;Python, Q.;Tavernier, S.;Van Doninck, W.;Van Mulders, P.;Van Parijs, I.;Brun, H.;Caillol, C.;Clerbaux, B.;De Lentdecker, G.;Delannoy, H.;Fasanella, G.;Favart, L.;Goldouzian, R.;Grebenyuk, A.;Karapostoli, G.;Lenzi, T.;Léonard, A.;Maerschalk, T.;Marinov, A.;Randle-conde, A.;Seva, T.;Vander Velde, C.;Vanlaer, P.;Yonamine, R.;Zenoni, F.;Zhang, F.;Cimmino, A.;Dobur, D.;Fagot, A.;Garcia, G.;Gul, M.;McCartin, J.;Poyraz, D.;Salva, S.;Schöfbeck, R.;Tytgat, M.;Van Driessche, W.;Yazgan, E.;Zaganidis, N.;Beluffi, C.;Bondu, O.;Brochet, S.;Bruno, G.;Caudron, A.;Ceard, L.;De Visscher, S.;Delaere, C.;Delcourt, M.;Forthomme, L.;Francois, B.;Giammanco, A.;Jafari, A.;Jez, P.;Komm, M.;Lemaitre, V.;Magitteri, A.;Mertens, A.;Musich, M.;Nuttens, C.;Piotrzkowski, K.;Quertenmont, L.;Selvaggi, M.;Vidal Marono, M.;Wertz, S.;Beliy, N.;Aldá Júnior, W. L.;Alves, F. L.;Alves, G. A.;Brito, L.;Correa Martins Junior, M.;Hensel, C.;Moraes, A.;Pol, M. E.;Rebello Teles, P.;Belchior Batista Das Chagas, E.;Carvalho, W.;Chinellato, J.;Custódio, A.;Da Costa, E. M.;Da Silveira, G. G.;De Jesus Damiao, D.;De Oliveira Martins, C.;Fonseca De Souza, S.;Huertas Guativa, L. M.;Malbouisson, H.;Matos Figueiredo, D.;Mora Herrera, C.;Mundim, L.;Nogima, H.;Prado Da Silva, W. L.;Santoro, A.;Sznajder, A.;Tonelli Manganote, E. J.;Vilela Pereira, A.;Ahuja, S.;Bernardes, C. A.;Dogra, S.;Fernandez Perez Tomei, T. R.;Gregores, E. M.;Mercadante, P. G.;Moon, C. S.;Novaes, S. F.;Padula, S. S.;Romero Abad, D.;Ruiz Vargas, J. C.;Aleksandrov, A.;Hadjiiska, R.;Iaydjiev, P.;Rodozov, M.;Stoykova, S.;Sultanov, G.;Vutova, M.;Dimitrov, A.;Glushkov, I.;Litov, L.;Pavlov, B.;Petkov, P.;Fang, W.;Ahmad, M.;Bian, J. G.;Chen, G. M.;Chen, H. S.;Chen, M.;Chen, Y.;Cheng, T.;Du, R.;Jiang, C. H.;Leggat, D.;Liu, Z.;Romeo, F.;Shaheen, S. M.;Spiezia, A.;Tao, J.;Wang, C.;Wang, Z.;Zhang, H.;Zhao, J.;Asawatangtrakuldee, C.;Ban, Y.;Li, Q.;Liu, S.;Mao, Y.;Qian, S. J.;Wang, D.;Xu, Z.;Avila, C.;Cabrera, A.;Chaparro Sierra, L. F.;Florez, C.;Gomez, J. P.;Ruiz Alvarez, J. D.;Sanabria, J. C.;Godinovic, N.;Lelas, D.;Puljak, I.;Ribeiro Cipriano, P. M.;Antunovic, Z.;Kovac, M.;Brigljevic, V.;Ferencek, D.;Kadija, K.;Luetic, J.;Micanovic, S.;Sudic, L.;Attikis, A.;Mavromanolakis, G.;Mousa, J.;Nicolaou, C.;Ptochos, F.;Razis, P. A.;Rykaczewski, H.;Finger, M., Jr.;Finger, M., Jr.;Carrera Jarrin, E.;Abdelalim, A. A.;El-khateeb, E.;Mahmoud, M. A.;Radi, A.;Calpas, B.;Kadastik, M.;Murumaa, M.;Perrini, L.;Raidal, M.;Tiko, A.;Veelken, C.;Eerola, P.;Pekkanen, J.;Voutilainen, M.;Härkönen, J.;Karimäki, V.;Kinnunen, R.;Lampén, T.;Lassila-Perini, K.;Lehti, S.;Lindén, T.;Luukka, P.;Peltola, T.;Tuominiemi, J.;Tuovinen, E.;Wendland, L.;Talvitie, J.;Tuuva, T.;Besancon, M.;Couderc, F.;Dejardin, M.;Denegri, D.;Fabbro, B.;Faure, J. L.;Favaro, C.;Ferri, F.;Ganjour, S.;Ghosh, S.;Givernaud, A.;Gras, P.;Hamel de Monchenault, G.;Jarry, P.;Locci, E.;Machet, M.;Malcles, J.;Rander, J.;Rosowsky, A.;Titov, M.;Zghiche, A.;Abdulsalam, A.;Antropov, I.;Baffioni, S.;Beaudette, F.;Busson, P.;Cadamuro, L.;Chapon, E.;Charlot, C.;Davignon, O.;Granier de Cassagnac, R.;Jo, M.;Lisniak, S.;Miné, P.;Naranjo, I. N.;Nguyen, M.;Ochando, C.;Ortona, G.;Paganini, P.;Pigard, P.;Regnard, S.;Salerno, R.;Sirois, Y.;Strebler, T.;Yilmaz, Y.;Zabi, A.;Agram, J. L.;Andrea, J.;Aubin, A.;Bloch, D.;Brom, J. M.;Buttignol, M.;Chabert, E. C.;Chanon, N.;Collard, C.;Conte, E.;Coubez, X.;Fontaine, J. C.;Gelé, D.;Goerlach, U.;Le Bihan, A. C.;Merlin, J. A.;Skovpen, K.;Van Hove, P.;Gadrat, S.;Beauceron, S.;Bernet, C.;Boudoul, G.;Bouvier, E.;Carrillo Montoya, C. A.;Chierici, R.;Contardo, D.;Courbon, B.;Depasse, P.;El Mamouni, H.;Fan, J.;Fay, J.;Gascon, S.;Gouzevitch, M.;Grenier, G.;Ille, B.;Lagarde, F.;Laktineh, I. B.;Lethuillier, M.;Mirabito, L.;Pequegnot, A. L.;Perries, S.;Popov, A.;Sabes, D.;Sordini, V.;Vander Donckt, M.;Verdier, P.;Viret, S.;Khvedelidze, A.;Tsamalaidze, Z.;Autermann, C.;Beranek, S.;Feld, L.;Heister, A.;Kiesel, M. K.;Klein, K.;Lipinski, M.;Ostapchuk, A.;Preuten, M.;Raupach, F.;Schael, S.;Schomakers, C.;Schulte, J. F.;Schulz, J.;Verlage, T.;Weber, H.;Zhukov, V.;Ata, M.;Brodski, M.;Dietz-Laursonn, E.;Duchardt, D.;Endres, M.;Erdmann, M.;Erdweg, S.;Esch, T.;Fischer, R.;Güth, A.;Hebbeker, T.;Heidemann, C.;Hoepfner, K.;Knutzen, S.;Merschmeyer, M.;Meyer, A.;Millet, P.;Mukherjee, S.;Olschewski, M.;Padeken, K.;Papacz, P.;Pook, T.;Radziej, M.;Reithler, H.;Rieger, M.;Scheuch, F.;Sonnenschein, L.;Teyssier, D.;Thüer, S.;Cherepanov, V.;Erdogan, Y.;Flügge, G.;Geenen, H.;Geisler, M.;Hoehle, F.;Kargoll, B.;Kress, T.;Künsken, A.;Lingemann, J.;Nehrkorn, A.;Nowack, A.;Nugent, I. M.;Pistone, C.;Pooth, O.;Stahl, A.;Aldaya Martin, M.;Asin, I.;Beernaert, K.;Behnke, O.;Behrens, U.;Bin Anuar, A. A.;Borras, K.;Campbell, A.;Connor, P.;Contreras-Campana, C.;Costanza, F.;Diez Pardos, C.;Dolinska, G.;Eckerlin, G.;Eckstein, D.;Eichhorn, T.;Gallo, E.;Garay Garcia, J.;Geiser, A.;Gizhko, A.;Grados Luyando, J. M.;Gunnellini, P.;Harb, A.;Hauk, J.;Hempel, M.;Jung, H.;Kalogeropoulos, A.;Karacheban, O.;Kasemann, M.;Kieseler, J.;Kleinwort, C.;Korol, I.;Lange, W.;Lelek, A.;Leonard, J.;Lipka, K.;Lobanov, A.;Lohmann, W.;Mankel, R.;Melzer-Pellmann, I. A.;Meyer, A. B.;Mittag, G.;Mnich, J.;Mussgiller, A.;Ntomari, E.;Pitzl, D.;Placakyte, R.;Raspereza, A.;Roland, B.;Sahin, M. Ö;Saxena, P.;Schoerner-Sadenius, T.;Seitz, C.;Spannagel, S.;Stefaniuk, N.;Trippkewitz, K. D.;Van Onsem, G. P.;Walsh, R.;Wissing, C.;Blobel, V.;Centis Vignali, M.;Draeger, A. R.;Dreyer, T.;Erfle, J.;Garutti, E.;Goebel, K.;Gonzalez, D.;Görner, M.;Haller, J.;Hoffmann, M.;Höing, R. S.;Junkes, A.;Klanner, R.;Kogler, R.;Kovalchuk, N.;Kurz, S.;Lapsien, T.;Lenz, T.;Marchesini, I.;Marconi, D.;Meyer, M.;Niedziela, M.;Nowatschin, D.;Ott, J.;Pantaleo, F.;Peiffer, T.;Perieanu, A.;Pietsch, N.;Poehlsen, J.;Sander, C.;Scharf, C.;Schleper, P.;Schlieckau, E.;Schmidt, A.;Schumann, S.;Schwandt, J.;Stadie, H.;Steinbrück, G.;Stober, F. M.;Stöver, M.;Tholen, H.;Troendle, D.;Usai, E.;Vanelderen, L.;Vanhoefer, A.;Vormwald, B.;Barth, C.;Baus, C.;Berger, J.;Butz, E.;Chwalek, T.;Colombo, F.;De Boer, W.;Dierlamm, A.;Fink, S.;Friese, R.;Giffels, M.;Gilbert, A.;Haitz, D.;Hartmann, F.;Heindl, S. M.;Husemann, U.;Katkov, I.;Kornmayer, A.;Lobelle Pardo, P.;Maier, B.;Mildner, H.;Mozer, M. U.;Müller, T.;Müller, T.;Plagge, M.;Quast, G.;Rabbertz, K.;Röcker, S.;Roscher, F.;Schröder, M.;Sieber, G.;Simonis, H. J.;Ulrich, R.;Wagner-Kuhr, J.;Wayand, S.;Weber, M.;Weiler, T.;Williamson, S.;Wöhrmann, C.;Wolf, R.;Anagnostou, G.;Daskalakis, G.;Geralis, T.;Giakoumopoulou, V. A.;Kyriakis, A.;Loukas, D.;Topsis-Giotis, I.;Agapitos, A.;Kesisoglou, S.;Panagiotou, A.;Saoulidou, N.;Tziaferi, E.;Evangelou, I.;Flouris, G.;Foudas, C.;Kokkas, P.;Loukas, N.;Manthos, N.;Papadopoulos, I.;Paradas, E.;Filipovic, N.;Bencze, G.;Hajdu, C.;Hidas, P.;Horvath, D.;Sikler, F.;Veszpremi, V.;Vesztergombi, G.;Zsigmond, A. J.;Beni, N.;Czellar, S.;Karancsi, J.;Molnar, J.;Szillasi, Z.;Bartók, M.;Makovec, A.;Raics, P.;Trocsanyi, Z. L.;Ujvari, B.;Bahinipati, S.;Choudhury, S.;Mal, P.;Mandal, K.;Nayak, A.;Sahoo, D. K.;Sahoo, N.;Swain, S. K.;Bansal, S.;Beri, S. B.;Bhatnagar, V.;Chawla, R.;Gupta, R.;Bhawandeep, U.;Kalsi, A. K.;Kaur, A.;Kaur, M.;Kumar, R.;Mehta, A.;Mittal, M.;Singh, J. B.;Walia, G.;Kumar, A.;Bhardwaj, A.;Choudhary, B. C.;Garg, R. B.;Keshri, S.;Malhotra, S.;Naimuddin, M.;Nishu, N.;Ranjan, K.;Sharma, R.;Sharma, V.;Bhattacharya, R.;Bhattacharya, S.;Chatterjee, K.;Dey, S.;Dutt, S.;Dutta, S.;Ghosh, S.;Majumdar, N.;Modak, A.;Mondal, K.;Mukhopadhyay, S.;Nandan, S.;Purohit, A.;Roy, A.;Roy, D.;Roy Chowdhury, S.;Sarkar, S.;Sharan, M.;Thakur, S.;Behera, P. K.;Chudasama, R.;Dutta, D.;Jha, V.;Kumar, V.;Mohanty, A. K.;Netrakanti, P. K.;Pant, L. M.;Shukla, P.;Topkar, A.;Aziz, T.;Banerjee, S.;Bhowmik, S.;Chatterjee, R. M.;Dewanjee, R. K.;Dugad, S.;Ganguly, S.;Guchait, M.;Gurtu, A.;Jain, S.;Kole, G.;Kumar, S.;Mahakud, B.;Maity, M.;Majumder, G.;Mazumdar, K.;Mitra, S.;Mohanty, G. B.;Parida, B.;Sarkar, T.;Sur, N.;Sutar, B.;Wickramage, N.;Chauhan, S.;Dube, S.;Kapoor, A.;Kothekar, K.;Rane, A.;Sharma, S.;Bakhshiansohi, H.;Behnamian, H.;Chenarani, S.;Eskandari Tadavani, E.;Etesami, S. M.;Fahim, A.;Khakzad, M.;Mohammadi Najafabadi, M.;Naseri, M.;Paktinat Mehdiabadi, S.;Rezaei Hosseinabadi, F.;Safarzadeh, B.;Zeinali, M.;Grunewald, M.;Abbrescia, M.;Calabria, C.;Caputo, C.;Colaleo, A.;Creanza, D.;Cristella, L.;De Filippis, N.;De Palma, M.;Fiore, L.;Iaselli, G.;Maggi, G.;Maggi, M.;Miniello, G.;My, S.;Nuzzo, S.;Pompili, A.;Pugliese, G.;Radogna, R.;Ranieri, A.;Selvaggi, G.;Silvestris, L.;Venditti, R.;Abbiendi, G.;Battilana, C.;Bonacorsi, D.;Braibant-Giacomelli, S.;Brigliadori, L.;Campanini, R.;Capiluppi, P.;Castro, A.;Cavallo, F. R.;Chhibra, S. S.;Codispoti, G.;Cuffiani, M.;Dallavalle, G. M.;Fabbri, F.;Fanfani, A.;Fasanella, D.;Giacomelli, P.;Grandi, C.;Guiducci, L.;Marcellini, S.;Masetti, G.;Montanari, A.;Navarria, F. L.;Perrotta, A.;Rossi, A. M.;Rovelli, T.;Siroli, G. P.;Tosi, N.;Albergo, S.;Chiorboli, M.;Costa, S.;Di Mattia, A.;Giordano, F.;Potenza, R.;Tricomi, A.;Tuve, C.;Barbagli, G.;Ciulli, V.;Civinini, C.;D'Alessandro, R.;Focardi, E.;Gori, V.;Lenzi, P.;Meschini, M.;Paoletti, S.;Sguazzoni, G.;Viliani, L.;Benussi, L.;Bianco, S.;Fabbri, F.;Piccolo, D.;Primavera, F.;Calvelli, V.;Ferro, F.;Lo Vetere, M.;Monge, M. R.;Robutti, E.;Tosi, S.;Brianza, L.;Brivio, F.;Dinardo, M. E.;Fiorendi, S.;Gennai, S.;Ghezzi, A.;Govoni, P.;Malvezzi, S.;Manzoni, R. A.;Marzocchi, B.;Menasce, D.;Moroni, L.;Paganoni, M.;Pedrini, D.;Pigazzini, S.;Ragazzi, S.;Tabarelli de Fatis, T.;Buontempo, S.;Cavallo, N.;De Nardo, G.;Di Guida, S.;Esposito, M.;Fabozzi, F.;Iorio, A. O. M.;Lanza, G.;Lista, L.;Meola, S.;Merola, M.;Paolucci, P.;Sciacca, C.;Thyssen, F.;Azzi, P.;Bacchetta, N.;Benato, L.;Bisello, D.;Boletti, A.;Carlin, R.;Carvalho Antunes De Oliveira, A.;Checchia, P.;Dall'Osso, M.;De Castro Manzano, P.;Dorigo, T.;Dosselli, U.;Gasparini, F.;Gasparini, U.;Gozzelino, A.;Lacaprara, S.;Margoni, M.;Meneguzzo, A. T.;Pazzini, J.;Pozzobon, N.;Ronchese, P.;Simonetto, F.;Torassa, E.;Tosi, M.;Zanetti, M.;Zotto, P.;Zucchetta, A.;Zumerle, G.;Braghieri, A.;Magnani, A.;Montagna, P.;Ratti, S. P.;Re, V.;Riccardi, C.;Salvini, P.;Vai, I.;Vitu, P.;Alunni Solestizi, L.;Bilei, G. M.;Ciangottini, D.;Fanò, L.;Lariccia, P.;Leonardi, R.;Mantovani, G.;Menichelli, M.;Saha, A.;Santocchia, A.;Androsov, K.;Azzurri, P.;Bagliesi, G.;Bernardini, J.;Boccali, T.;Castaldi, R.;Ciocci, M. A.;Dell'Orso, R.;Donato, S.;Fedi, G.;Giassi, A.;Grippo, M. T.;Ligabue, F.;Lomtadze, T.;Martini, L.;Messineo, A.;Palla, F.;Rizzi, A.;Savoy-Navarro, A.;Spagnolo, P.;Tenchini, R.;Tonelli, G.;Venturi, A.;Verdini, P. G.;Barone, L.;Cavallari, F.;Cipriani, M.;D'Imperio, G.;Del Re, D.;Diemoz, M.;Gelli, S.;Jorda, C.;Longo, E.;Margaroli, F.;Meridiani, P.;Organtini, G.;Paramatti, R.;Preiato, F.;Rahatlou, S.;Rovelli, C.;Santanastasio, F.;Amapane, N.;Arcidiacono, R.;Argiro, S.;Arneodo, M.;Bartosik, N.;Bellan, R.;Biino, C.;Cartiglia, N.;Costa, M.;Covarelli, R.;Degano, A.;Demaria, N.;Finco, L.;Kiani, B.;Mariotti, C.;Maselli, S.;Migliore, E.;Monaco, V.;Monteil, E.;Obertino, M. M.;Pacher, L.;Pastrone, N.;Pelliccioni, M.;Pinna Angioni, G. L.;Ravera, F.;Romero, A.;Ruspa, M.;Sacchi, R.;Sola, V.;Solano, A.;Staiano, A.;Traczyk, P.;Belforte, S.;Candelise, V.;Casarsa, M.;Cossutti, F.;Della Ricca, G.;La Licata, C.;Schizzi, A.;Zanetti, A.;Kim, D. H.;Kim, G. N.;Kim, M. S.;Lee, S.;Lee, S. W.;Oh, Y. D.;Sekmen, S.;Son, D. C.;Yang, Y. C.;Kim, H.;Brochero Cifuentes, J. A.;Kim, T. J.;Cho, S.;Choi, S.;Go, Y.;Gyun, D.;Ha, S.;Hong, B.;Jo, Y.;Kim, Y.;Lee, B.;Lee, K.;Lee, K. S.;Lee, S.;Lim, J.;Park, S. K.;Roh, Y.;Almond, J.;Kim, J.;Seo, S. H.;Yang, U.;Yoo, H. D.;Yu, G. B.;Choi, M.;Kim, H.;Kim, H.;Kim, J. H.;Lee, J. S. H.;Park, I. C.;Ryu, G.;Ryu, M. S.;Choi, Y.;Goh, J.;Kim, D.;Kwon, E.;Lee, J.;Yu, I.;Dudenas, V.;Juodagalvis, A.;Vaitkus, J.;Ahmed, I.;Ibrahim, Z. A.;Komaragiri, J. R.;Md Ali, M. A. B.;Mohamad Idris, F.;Wan Abdullah, W. A. T.;Yusli, M. N.;Zolkapli, Z.;Casimiro Linares, E.;Castilla-Valdez, H.;De La Cruz-Burelo, E.;Heredia-De La Cruz, I.;Hernandez-Almada, A.;Lopez-Fernandez, R.;Mejia Guisao, J.;Sanchez-Hernandez, A.;Carrillo Moreno, S.;Vazquez Valencia, F.;Pedraza, I.;Salazar Ibarguen, H. A.;Uribe Estrada, C.;Morelos Pineda, A.;Krofcheck, D.;Butler, P. H.;Ahmad, A.;Ahmad, M.;Hassan, Q.;Hoorani, H. R.;Khan, W. A.;Khurshid, T.;Shoaib, M.;Waqas, M.;Bialkowska, H.;Bluj, M.;Boimska, B.;Frueboes, T.;Górski, M.;Kazana, M.;Nawrocki, K.;Romanowska-Rybinska, K.;Szleper, M.;Zalewski, P.;Bunkowski, K.;Byszuk, A.;Doroba, K.;Kalinowski, A.;Konecki, M.;Krolikowski, J.;Misiura, M.;Olszewski, M.;Walczak, M.;Bargassa, P.;Beirão Da Cruz E Silva, C.;Di Francesco, A.;Faccioli, P.;Ferreira Parracho, P. G.;Gallinaro, M.;Hollar, J.;Leonardo, N.;Lloret Iglesias, L.;Nemallapudi, M. V.;Nguyen, F.;Rodrigues Antunes, J.;Seixas, J.;Toldaiev, O.;Vadruccio, D.;Varela, J.;Vischia, P.;Afanasiev, S.;Bunin, P.;Gavrilenko, M.;Golutvin, I.;Gorbunov, I.;Kamenev, A.;Karjavin, V.;Lanev, A.;Malakhov, A.;Matveev, V.;Moisenz, P.;Palichik, V.;Perelygin, V.;Shmatov, S.;Shulha, S.;Skatchkov, N.;Smirnov, V.;Voytishin, N.;Zarubin, A.;Chtchipounov, L.;Golovtsov, V.;Ivanov, Y.;Kim, V.;Kuznetsova, E.;Murzin, V.;Oreshkin, V.;Sulimov, V.;Vorobyev, A.;Andreev, Y.;Dermenev, A.;Gninenko, S.;Golubev, N.;Karneyeu, A.;Kirsanov, M.;Krasnikov, N.;Pashenkov, A.;Tlisov, D.;Toropin, A.;Epshteyn, V.;Gavrilov, V.;Lychkovskaya, N.;Popov, V.;Pozdnyakov, I.;Safronov, G.;Spiridonov, A.;Toms, M.;Vlasov, E.;Zhokin, A.;Chadeeva, M.;Markin, O.;Tarkovskii, E.;Andreev, V.;Azarkin, M.;Dremin, I.;Kirakosyan, M.;Leonidov, A.;Rusakov, S. V.;Terkulov, A.;Baskakov, A.;Belyaev, A.;Boos, E.;Dubinin, M.;Dudko, L.;Ershov, A.;Gribushin, A.;Klyukhin, V.;Kodolova, O.;Lokhtin, I.;Miagkov, I.;Obraztsov, S.;Petrushanko, S.;Savrin, V.;Snigirev, A.;Azhgirey, I.;Bayshev, I.;Bitioukov, S.;Elumakhov, D.;Kachanov, V.;Kalinin, A.;Konstantinov, D.;Krychkine, V.;Petrov, V.;Ryutin, R.;Sobol, A.;Troshin, S.;Tyurin, N.;Uzunian, A.;Volkov, A.;Adzic, P.;Cirkovic, P.;Devetak, D.;Milosevic, J.;Rekovic, V.;Alcaraz Maestre, J.;Calvo, E.;Cerrada, M.;Chamizo Llatas, M.;Colino, N.;De La Cruz, B.;Delgado Peris, A.;Escalante Del Valle, A.;Fernandez Bedoya, C.;Fernández Ramos, J. P.;Flix, J.;Fouz, M. C.;Garcia-Abia, P.;Gonzalez Lopez, O.;Goy Lopez, S.;Hernandez, J. M.;Josa, M. I.;Navarro De Martino, E.;Pérez-Calero Yzquierdo, A.;Puerta Pelayo, J.;Quintario Olmeda, A.;Redondo, I.;Romero, L.;Soares, M. S.;de Trocóniz, J. F.;Missiroli, M.;Moran, D.;Cuevas, J.;Fernandez Menendez, J.;Gonzalez Caballero, I.;Palencia Cortezon, E.;Sanchez Cruz, S.;Vizan Garcia, J. M.;Cabrillo, I. J.;Calderon, A.;Castiñeiras De Saa, J. R.;Curras, E.;Fernandez, M.;Garcia-Ferrero, J.;Gomez, G.;Lopez Virto, A.;Marco, J.;Martinez Rivero, C.;Matorras, F.;Piedra Gomez, J.;Rodrigo, T.;Ruiz-Jimeno, A.;Scodellaro, L.;Trevisani, N.;Vila, I.;Vilar Cortabitarte, R.;Abbaneo, D.;Auffray, E.;Auzinger, G.;Bachtis, M.;Baillon, P.;Ball, A. H.;Barney, D.;Bloch, P.;Bocci, A.;Bonato, A.;Botta, C.;Camporesi, T.;Castello, R.;Cepeda, M.;Cerminara, G.;D'Alfonso, M.;d'Enterria, D.;Dabrowski, A.;Daponte, V.;David, A.;De Gruttola, M.;De Guio, F.;De Roeck, A.;Di Marco, E.;Dobson, M.;Dordevic, M.;Dorney, B.;du Pree, T.;Duggan, D.;Dünser, M.;Dupont, N.;Elliott-Peisert, A.;Fartoukh, S.;Franzoni, G.;Fulcher, J.;Funk, W.;Gigi, D.;Gill, K.;Girone, M.;Glege, F.;Gundacker, S.;Guthoff, M.;Hammer, J.;Harris, P.;Hegeman, J.;Innocente, V.;Janot, P.;Kirschenmann, H.;Knünz, V.;Kortelainen, M. J.;Kousouris, K.;Krammer, M.;Lecoq, P.;Lourenço, C.;Lucchini, M. T.;Magini, N.;Malgeri, L.;Mannelli, M.;Martelli, A.;Meijers, F.;Mersi, S.;Meschi, E.;Moortgat, F.;Morovic, S.;Mulders, M.;Neugebauer, H.;Orfanelli, S.;Orsini, L.;Pape, L.;Perez, E.;Peruzzi, M.;Petrilli, A.;Petrucciani, G.;Pfeiffer, A.;Pierini, M.;Racz, A.;Reis, T.;Rolandi, G.;Rovere, M.;Ruan, M.;Sakulin, H.;Sauvan, J. B.;Schäfer, C.;Schwick, C.;Seidel, M.;Sharma, A.;Silva, P.;Simon, M.;Sphicas, P.;Steggemann, J.;Stoye, M.;Takahashi, Y.;Treille, D.;Triossi, A.;Tsirou, A.;Veckalns, V.;Veres, G. I.;Wardle, N.;Zagozdzinska, A.;Zeuner, W. D.;Bertl, W.;Deiters, K.;Erdmann, W.;Horisberger, R.;Ingram, Q.;Kaestli, H. C.;Kotlinski, D.;Langenegger, U.;Rohe, T.;Bachmair, F.;Bäni, L.;Bianchini, L.;Casal, B.;Dissertori, G.;Dittmar, M.;Donegà, M.;Eller, P.;Grab, C.;Heidegger, C.;Hits, D.;Hoss, J.;Kasieczka, G.;Lecomte, P.;Lustermann, W.;Mangano, B.;Marionneau, M.;Martinez Ruiz del Arbol, P.;Masciovecchio, M.;Meinhard, M. T.;Meister, D.;Micheli, F.;Musella, P.;Nessi-Tedaldi, F.;Pandolfi, F.;Pata, J.;Pauss, F.;Perrin, G.;Perrozzi, L.;Quittnat, M.;Rossini, M.;Schönenberger, M.;Starodumov, A.;Takahashi, M.;Tavolaro, V. R.;Theofilatos, K.;Wallny, R.;Aarrestad, T. K.;Amsler, C.;Caminada, L.;Canelli, M. F.;Chiochia, V.;De Cosa, A.;Galloni, C.;Hinzmann, A.;Hreus, T.;Kilminster, B.;Lange, C.;Ngadiuba, J.;Pinna, D.;Rauco, G.;Robmann, P.;Salerno, D.;Yang, Y.;Chen, K. H.;Doan, T. H.;Jain, S.;Khurana, R.;Konyushikhin, M.;Kuo, C. M.;Lin, W.;Lu, Y. J.;Pozdnyakov, A.;Yu, S. S.;Kumar, A.;Chang, P.;Chang, Y. H.;Chang, Y. W.;Chao, Y.;Chen, K. F.;Chen, P. H.;Dietz, C.;Fiori, F.;Hou, W. S.;Hsiung, Y.;Liu, Y. F.;Lu, R. S.;Miñano Moya, M.;Paganis, E.;Tsai, J. F.;Tzeng, Y. M.;Asavapibhop, B.;Singh, G.;Srimanobhas, N.;Suwonjandee, N.;Adiguzel, A.;Cerci, S.;Damarseckin, S.;Demiroglu, Z. S.;Dozen, C.;Dumanoglu, I.;Girgis, S.;Gokbulut, G.;Guler, Y.;Gurpinar, E.;Hos, I.;Kangal, E. E.;Kayis Topaksu, A.;Onengut, G.;Ozdemir, K.;Sunar Cerci, D.;Tali, B.;Zorbilmez, C.;Bilin, B.;Bilmis, S.;Isildak, B.;Karapinar, G.;Yalvac, M.;Zeyrek, M.;Gülmez, E.;Kaya, M.;Kaya, O.;Yetkin, E. A.;Yetkin, T.;Cakir, A.;Cankocak, K.;Sen, S.;Vardarli, F. I.;Grynyov, B.;Levchuk, L.;Sorokin, P.;Aggleton, R.;Ball, F.;Beck, L.;Brooke, J. J.;Burns, D.;Clement, E.;Cussans, D.;Flacher, H.;Goldstein, J.;Grimes, M.;Heath, G. P.;Heath, H. F.;Jacob, J.;Kreczko, L.;Lucas, C.;Meng, Z.;Newbold, D. M.;Paramesvaran, S.;Poll, A.;Sakuma, T.;Seif El Nasr-storey, S.;Senkin, S.;Smith, D.;Smith, V. J.;Bell, K. W.;Belyaev, A.;Brew, C.;Brown, R. M.;Calligaris, L.;Cieri, D.;Cockerill, D. J. A.;Coughlan, J. A.;Harder, K.;Harper, S.;Olaiya, E.;Petyt, D.;Shepherd-Themistocleous, C. H.;Thea, A.;Tomalin, I. R.;Williams, T.;Baber, M.;Bainbridge, R.;Buchmuller, O.;Bundock, A.;Burton, D.;Casasso, S.;Citron, M.;Colling, D.;Corpe, L.;Dauncey, P.;Davies, G.;De Wit, A.;Della Negra, M.;Dunne, P.;Elwood, A.;Futyan, D.;Haddad, Y.;Hall, G.;Iles, G.;Lane, R.;Laner, C.;Lucas, R.;Lyons, L.;Magnan, A. M.;Malik, S.;Mastrolorenzo, L.;Nash, J.;Nikitenko, A.;Pela, J.;Penning, B.;Pesaresi, M.;Raymond, D. M.;Richards, A.;Rose, A.;Seez, C.;Tapper, A.;Uchida, K.;Vazquez Acosta, M.;Virdee, T.;Zenz, S. C.;Cole, J. E.;Hobson, P. R.;Khan, A.;Kyberd, P.;Leslie, D.;Reid, I. D.;Symonds, P.;Teodorescu, L.;Turner, M.;Borzou, A.;Call, K.;Dittmann, J.;Hatakeyama, K.;Liu, H.;Pastika, N.;Charaf, O.;Cooper, S. I.;Henderson, C.;Rumerio, P.;Arcaro, D.;Avetisyan, A.;Bose, T.;Gastler, D.;Rankin, D.;Richardson, C.;Rohlf, J.;Sulak, L.;Zou, D.;Benelli, G.;Berry, E.;Cutts, D.;Ferapontov, A.;Garabedian, A.;Hakala, J.;Heintz, U.;Jesus, O.;Laird, E.;Landsberg, G.;Mao, Z.;Narain, M.;Piperov, S.;Sagir, S.;Spencer, E.;Syarif, R.;Breedon, R.;Breto, G.;Burns, D.;Calderon De La Barca Sanchez, M.;Chauhan, S.;Chertok, M.;Conway, J.;Conway, R.;Cox, P. T.;Erbacher, R.;Flores, C.;Funk, G.;Gardner, M.;Ko, W.;Lander, R.;McLean, C.;Mulhearn, M.;Pellett, D.;Pilot, J.;Ricci-Tam, F.;Shalhout, S.;Smith, J.;Squires, M.;Stolp, D.;Tripathi, M.;Wilbur, S.;Yohay, R.;Cousins, R.;Everaerts, P.;Florent, A.;Hauser, J.;Ignatenko, M.;Saltzberg, D.;Takasugi, E.;Valuev, V.;Weber, M.;Burt, K.;Clare, R.;Ellison, J.;Gary, J. W.;Hanson, G.;Heilman, J.;Jandir, P.;Kennedy, E.;Lacroix, F.;Long, O. R.;Malberti, M.;Olmedo Negrete, M.;Paneva, M. I.;Shrinivas, A.;Wei, H.;Wimpenny, S.;Yates, B. R.;Branson, J. G.;Cerati, G. B.;Cittolin, S.;D'Agnolo, R. T.;Derdzinski, M.;Gerosa, R.;Holzner, A.;Kelley, R.;Klein, D.;Letts, J.;Macneill, I.;Olivito, D.;Padhi, S.;Pieri, M.;Sani, M.;Sharma, V.;Simon, S.;Tadel, M.;Vartak, A.;Wasserbaech, S.;Welke, C.;Wood, J.;Würthwein, F.;Yagil, A.;Zevi Della Porta, G.;Bhandari, R.;Bradmiller-Feld, J.;Campagnari, C.;Dishaw, A.;Dutta, V.;Flowers, K.;Franco Sevilla, M.;Geffert, P.;George, C.;Golf, F.;Gouskos, L.;Gran, J.;Heller, R.;Incandela, J.;McColl, N.;Mullin, S. D.;Ovcharova, A.;Richman, J.;Stuart, D.;Suarez, I.;West, C.;Yoo, J.;Anderson, D.;Apresyan, A.;Bendavid, J.;Bornheim, A.;Bunn, J.;Chen, Y.;Duarte, J.;Mott, A.;Newman, H. B.;Pena, C.;Spiropulu, M.;Vlimant, J. R.;Xie, S.;Zhu, R. Y.;Andrews, M. B.;Azzolini, V.;Calamba, A.;Carlson, B.;Ferguson, T.;Paulini, M.;Russ, J.;Sun, M.;Vogel, H.;Vorobiev, I.;Cumalat, J. P.;Ford, W. T.;Jensen, F.;Johnson, A.;Krohn, M.;Mulholland, T.;Stenson, K.;Wagner, S. R.;Alexander, J.;Chatterjee, A.;Chaves, J.;Chu, J.;Dittmer, S.;Eggert, N.;Mirman, N.;Nicolas Kaufman, G.;Patterson, J. R.;Rinkevicius, A.;Ryd, A.;Skinnari, L.;Sun, W.;Tan, S. M.;Tao, Z.;Teo, W. D.;Thom, J.;Thompson, J.;Tucker, J.;Weng, Y.;Wittich, P.;Winn, D.;Abdullin, S.;Albrow, M.;Apollinari, G.;Banerjee, S.;Bauerdick, L. A. T.;Beretvas, A.;Berryhill, J.;Bhat, P. C.;Bolla, G.;Burkett, K.;Butler, J. N.;Cheung, H. W. K.;Chlebana, F.;Cihangir, S.;Cremonesi, M.;Elvira, V. D.;Fisk, I.;Freeman, J.;Gottschalk, E.;Gray, L.;Green, D.;Grünendahl, S.;Gutsche, O.;Hare, D.;Harris, R. M.;Hasegawa, S.;Hirschauer, J.;Hu, Z.;Jayatilaka, B.;Jindariani, S.;Johnson, M.;Joshi, U.;Klima, B.;Kreis, B.;Lammel, S.;Linacre, J.;Lincoln, D.;Lipton, R.;Liu, T.;Lopes De Sá, R.;Lykken, J.;Maeshima, K.;Marraffino, J. M.;Maruyama, S.;Mason, D.;McBride, P.;Merkel, P.;Mrenna, S.;Nahn, S.;Newman-Holmes, C.;O'Dell, V.;Pedro, K.;Prokofyev, O.;Rakness, G.;Ristori, L.;Sexton-Kennedy, E.;Soha, A.;Spalding, W. J.;Spiegel, L.;Stoynev, S.;Strobbe, N.;Taylor, L.;Tkaczyk, S.;Tran, N. V.;Uplegger, L.;Vaandering, E. W.;Vernieri, C.;Verzocchi, M.;Vidal, R.;Wang, M.;Weber, H. A.;Whitbeck, A.;Acosta, D.;Avery, P.;Bortignon, P.;Bourilkov, D.;Brinkerhoff, A.;Carnes, A.;Carver, M.;Curry, D.;Das, S.;Field, R. D.;Furic, I. K.;Konigsberg, J.;Korytov, A.;Ma, P.;Matchev, K.;Mei, H.;Milenovic, P.;Mitselmakher, G.;Rank, D.;Shchutska, L.;Sperka, D.;Thomas, L.;Wang, J.;Wang, S.;Yelton, J.;Linn, S.;Markowitz, P.;Martinez, G.;Rodriguez, J. L.;Ackert, A.;Adams, J. R.;Adams, T.;Askew, A.;Bein, S.;Diamond, B.;Hagopian, S.;Hagopian, V.;Johnson, K. F.;Khatiwada, A.;Prosper, H.;Santra, A.;Weinberg, M.;Baarmand, M. M.;Bhopatkar, V.;Colafranceschi, S.;Hohlmann, M.;Kalakhety, H.;Noonan, D.;Roy, T.;Yumiceva, F.;Adams, M. R.;Apanasevich, L.;Berry, D.;Betts, R. R.;Bucinskaite, I.;Cavanaugh, R.;Evdokimov, O.;Gauthier, L.;Gerber, C. E.;Hofman, D. J.;Kurt, P.;O'Brien, C.;Sandoval Gonzalez, I. D.;Turner, P.;Varelas, N.;Wu, Z.;Zakaria, M.;Zhang, J.;Bilki, B.;Clarida, W.;Dilsiz, K.;Durgut, S.;Gandrajula, R. P.;Haytmyradov, M.;Khristenko, V.;Merlo, J. P.;Mermerkaya, H.;Mestvirishvili, A.;Moeller, A.;Nachtman, J.;Ogul, H.;Onel, Y.;Ozok, F.;Penzo, A.;Snyder, C.;Tiras, E.;Wetzel, J.;Yi, K.;Anderson, I.;Blumenfeld, B.;Cocoros, A.;Eminizer, N.;Fehling, D.;Feng, L.;Gritsan, A. V.;Maksimovic, P.;Osherson, M.;Roskes, J.;Sarica, U.;Swartz, M.;Xiao, M.;Xin, Y.;You, C.;Al-bataineh, A.;Baringer, P.;Bean, A.;Bruner, C.;Castle, J.;Kenny, R. P., III;Kropivnitskaya, A.;Majumder, D.;Malek, M.;McBrayer, W.;Murray, M.;Sanders, S.;Stringer, R.;Wang, Q.;Ivanov, A.;Kaadze, K.;Khalil, S.;Makouski, M.;Maravin, Y.;Mohammadi, A.;Saini, L. K.;Skhirtladze, N.;Toda, S.;Lange, D.;Rebassoo, F.;Wright, D.;Anelli, C.;Baden, A.;Baron, O.;Belloni, A.;Calvert, B.;Eno, S. C.;Ferraioli, C.;Gomez, J. A.;Hadley, N. J.;Jabeen, S.;Kellogg, R. G.;Kolberg, T.;Kunkle, J.;Lu, Y.;Mignerey, A. C.;Shin, Y. H.;Skuja, A.;Tonjes, M. B.;Tonwar, S. C.;Apyan, A.;Barbieri, R.;Baty, A.;Bi, R.;Bierwagen, K.;Brandt, S.;Busza, W.;Cali, I. A.;Demiragli, Z.;Di Matteo, L.;Gomez Ceballos, G.;Goncharov, M.;Gulhan, D.;Hsu, D.;Iiyama, Y.;Innocenti, G. M.;Klute, M.;Kovalskyi, D.;Krajczar, K.;Lai, Y. S.;Lee, Y. J.;Levin, A.;Luckey, P. D.;Marini, A. C.;McGinn, C.;Mironov, C.;Narayanan, S.;Niu, X.;Paus, C.;Roland, C.;Roland, G.;Salfeld-Nebgen, J.;Stephans, G. S. F.;Sumorok, K.;Tatar, K.;Varma, M.;Velicanu, D.;Veverka, J.;Wang, J.;Wang, T. W.;Wyslouch, B.;Yang, M.;Zhukova, V.;Benvenuti, A. C.;Dahmes, B.;Evans, A.;Finkel, A.;Gude, A.;Hansen, P.;Kalafut, S.;Kao, S. C.;Klapoetke, K.;Kubota, Y.;Lesko, Z.;Mans, J.;Nourbakhsh, S.;Ruckstuhl, N.;Rusack, R.;Tambe, N.;Turkewitz, J.;Acosta, J. G.;Oliveros, S.;Avdeeva, E.;Bartek, R.;Bloom, K.;Bose, S.;Claes, D. R.;Dominguez, A.;Fangmeier, C.;Gonzalez Suarez, R.;Kamalieddin, R.;Knowlton, D.;Kravchenko, I.;Meier, F.;Monroy, J.;Siado, J. E.;Snow, G. R.;Stieger, B.;Alyari, M.;Dolen, J.;George, J.;Godshalk, A.;Harrington, C.;Iashvili, I.;Kaisen, J.;Kharchilava, A.;Kumar, A.;Parker, A.;Rappoccio, S.;Roozbahani, B.;Alverson, G.;Barberis, E.;Baumgartel, D.;Chasco, M.;Hortiangtham, A.;Massironi, A.;Morse, D. M.;Nash, D.;Orimoto, T.;Teixeira De Lima, R.;Trocino, D.;Wang, R. J.;Wood, D.;Bhattacharya, S.;Hahn, K. A.;Kubik, A.;Low, J. F.;Mucia, N.;Odell, N.;Pollack, B.;Schmitt, M. H.;Sung, K.;Trovato, M.;Velasco, M.;Dev, N.;Hildreth, M.;Hurtado Anampa, K.;Jessop, C.;Karmgard, D. J.;Kellams, N.;Lannon, K.;Marinelli, N.;Meng, F.;Mueller, C.;Musienko, Y.;Planer, M.;Reinsvold, A.;Ruchti, R.;Rupprecht, N.;Smith, G.;Taroni, S.;Valls, N.;Wayne, M.;Wolf, M.;Woodard, A.;Alimena, J.;Antonelli, L.;Brinson, J.;Bylsma, B.;Durkin, L. S.;Flowers, S.;Francis, B.;Hart, A.;Hill, C.;Hughes, R.;Ji, W.;Liu, B.;Luo, W.;Puigh, D.;Rodenburg, M.;Winer, B. L.;Wulsin, H. W.;Driga, O.;Elmer, P.;Hardenbrook, J.;Hebda, P.;Marlow, D.;Medvedeva, T.;Mooney, M.;Olsen, J.;Palmer, C.;Piroué, P.;Stickland, D.;Tully, C.;Zuranski, A.;Malik, S.;Barker, A.;Barnes, V. E.;Benedetti, D.;Folgueras, S.;Gutay, L.;Jha, M. K.;Jones, M.;Jung, A. W.;Jung, K.;Miller, D. H.;Neumeister, N.;Radburn-Smith, B. C.;Shi, X.;Sun, J.;Svyatkovskiy, A.;Wang, F.;Xie, W.;Xu, L.;Parashar, N.;Stupak, J.;Adair, A.;Akgun, B.;Chen, Z.;Ecklund, K. M.;Geurts, F. J. M.;Guilbaud, M.;Li, W.;Michlin, B.;Northup, M.;Padley, B. P.;Redjimi, R.;Roberts, J.;Rorie, J.;Tu, Z.;Zabel, J.;Betchart, B.;Bodek, A.;de Barbaro, P.;Demina, R.;Duh, Y. T.;Eshaq, Y.;Ferbel, T.;Galanti, M.;Garcia-Bellido, A.;Han, J.;Hindrichs, O.;Khukhunaishvili, A.;Lo, K. H.;Tan, P.;Verzetti, M.;Chou, J. P.;Contreras-Campana, E.;Gershtein, Y.;Gómez Espinosa, T. A.;Halkiadakis, E.;Heindl, M.;Hidas, D.;Hughes, E.;Kaplan, S.;Kunnawalkam Elayavalli, R.;Kyriacou, S.;Lath, A.;Nash, K.;Saka, H.;Salur, S.;Schnetzer, S.;Sheffield, D.;Somalwar, S.;Stone, R.;Thomas, S.;Thomassen, P.;Walker, M.;Foerster, M.;Heideman, J.;Riley, G.;Rose, K.;Spanier, S.;Thapa, K.;Bouhali, O.;Castaneda Hernandez, A.;Celik, A.;Dalchenko, M.;De Mattia, M.;Delgado, A.;Dildick, S.;Eusebi, R.;Gilmore, J.;Huang, T.;Juska, E.;Kamon, T.;Krutelyov, V.;Mueller, R.;Pakhotin, Y.;Patel, R.;Perloff, A.;Perniè, L.;Rathjens, D.;Rose, A.;Safonov, A.;Tatarinov, A.;Ulmer, K. A.;Akchurin, N.;Cowden, C.;Damgov, J.;Dragoiu, C.;Dudero, P. R.;Faulkner, J.;Kunori, S.;Lamichhane, K.;Lee, S. W.;Libeiro, T.;Undleeb, S.;Volobouev, I.;Wang, Z.;Delannoy, A. G.;Greene, S.;Gurrola, A.;Janjam, R.;Johns, W.;Maguire, C.;Melo, A.;Ni, H.;Sheldon, P.;Tuo, S.;Velkovska, J.;Xu, Q.;Arenton, M. W.;Barria, P.;Cox, B.;Goodell, J.;Hirosky, R.;Ledovskoy, A.;Li, H.;Neu, C.;Sinthuprasith, T.;Sun, X.;Wang, Y.;Wolfe, E.;Xia, F.;Clarke, C.;Harr, R.;Karchin, P. E.;Kottachchi Kankanamge Don, C.;Lamichhane, P.;Sturdy, J.;Belknap, D. A.;Dasu, S.;Dodd, L.;Duric, S.;Gomber, B.;Grothe, M.;Herndon, M.;Hervé, A.;Klabbers, P.;Lanaro, A.;Levine, A.;Long, K.;Loveless, R.;Ojalvo, I.;Perry, T.;Pierro, G. A.;Polese, G.;Ruggles, T.;Savin, A.;Sharma, A.;Smith, N.;Smith, W. H.;Taylor, D.;Verwilligen, P.;Woods, N.
Keywords: Cms; Multijets; Physics; Supersymmetry